Knowledge, awareness and attitudes towards retinopathy of prematurity among Jordanian pediatricians: a cross sectional descriptive study - Abu-Yaghi, Nakhleh; Meqbil, Jehad; Helwa, Layth; Al-imam, Mahmood; Zghoul, Ayat; Hammad, Noor; Awad, Rana; AL- Obaidy, Abdul Hakeem; Abusalah, Bisan; Elfalah, Mutasem; et al. (Jordan Medical Journal, 2023)
Abstract Background: Retinopathy of prematurity (ROP) is a preventable cause of childhood blindness. This study aims to measure knowledge, awareness and attitudes of Jordanian pediatricians towards ROP screening and treatment protocols, and to identify any barriers concerning referrals to specialized care. Methods: This is a cross-sectional non-interventional descriptive study. A self-administered semi- structured electronic questionnaire was designed to assess the knowledge, attitude and practice patterns of responders and was disseminated via social media and direct contact with pediatricians in governmental and private hospitals from all over the country and collected between June and November of 2022. The questionnaire included questions regarding demographics, level of education, practice details and knowledge regarding ROP. Results: A total of 85 responders from all levels completed the questionnaire. Most of the responders (78 (91.8%)) identified the main risk factors of ROP as low birth weight and gestational age and maintained that timely screening should be performed by an ophthalmologist. Fifty-nine pediatricians (69.4%) were sure that ROP is preventable and 62 (72.9%) identified both laser and anti- vascular endothelial growth factor injections as possible modalities of treatment. Thirty participants (35.3%) faced real limitations reaching ophthalmologists for a reliable ROP consultation. Conclusions: This study demonstrated a high level of awareness of ROP among Jordanian pediatricians of all levels, although some gaps pertaining to the accurate timing of screening still exist. There are identifiable limitations facing Jordanian pediatricians to reach a reliable ophthalmic service to screen and manage referred cases. A unified nation-wide ROP screening protocol with clear access to standardized ophthalmic care is necessary to reduce the challenges facing the screening and management process and by extension, the burden of this preventable disease.